Intersections of history, memories and education: constructing citizenship in Latin America - Panduro Llerena, Reynaldo (2024)
An interview with Dr. Jaime Vito Paredes, PhD in Contemporary Latin American History from the University of Alcalá, Spain, is presented. He holds a Master’s degree in History from the Pontificia Universidad Católica de Valparaíso (PUCV). Academic of the Institute of History of the PUCV, he specializes in the history of historiography, theory of history, and economic and social history of Latin America. His research focuses on liberalism and state financing in the nineteenth century and has published on the history of Catholicism in Chile during the same century. Since 2003, he has participated in binational historiographical projects directed by Dr. Eduardo Cavieres, collaborating with scholars from Argentina, Bolivia, Chile and Peru. He also coordinates the Eduardo Cavieres Figueroa Chair at the PUCV.